2019
DOI: 10.1186/s13756-019-0578-3
|View full text |Cite
|
Sign up to set email alerts
|

Molecular epidemiological analysis and risk factors for acquisition of carbapenemase-producing Enterobacter cloacae complex in a Japanese university hospital

Abstract: Background To clarify the molecular epidemiology of carbapenem-resistant Enterobacter cloacae complex (CREC) and the risk factors for acquisition of carbapenemase-producing E. cloacae complex (CPEC). Methods Using clinical CREC isolates detected in a Japanese university hospital over 4 years, carbapenemase production was screened with phenotypic methods. Carbapenemase genes were analysed by PCR and sequencing. Molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 28 publications
(28 reference statements)
1
16
1
Order By: Relevance
“…Class 1-integron-harboring bla IMP-68 in pTMTA63632 (Fig. 1), which was assigned to In1702 in the INTEGRALL database (22), was similar to previously reported IMP genes harboring class 1 integrons, as the gene cassettes were located between intI1 and qacEΔ1-sul1 (10, 23, 24). Specifically, In1702 was compared with the class 1 integrons harbored by pNUH14_ECL028_1 and pIMP-A2015-49 plasmids previously found in Japan (24), which carried IMP-1 and IMP-11, respectively (Fig.…”
Section: Observationsupporting
confidence: 84%
“…Class 1-integron-harboring bla IMP-68 in pTMTA63632 (Fig. 1), which was assigned to In1702 in the INTEGRALL database (22), was similar to previously reported IMP genes harboring class 1 integrons, as the gene cassettes were located between intI1 and qacEΔ1-sul1 (10, 23, 24). Specifically, In1702 was compared with the class 1 integrons harbored by pNUH14_ECL028_1 and pIMP-A2015-49 plasmids previously found in Japan (24), which carried IMP-1 and IMP-11, respectively (Fig.…”
Section: Observationsupporting
confidence: 84%
“…1,2 During the last decade, the emergence of carbapenem-resistant Enterobacteriaceae (CRE), which led to limited treatment options, has become the main cause of clinical anti-infective treatment failure. 3,4 It is worth noting that carbapenem-resistant Enterobacter cloacae (CR-ECL), which is one of the most common species that has been focused on in studies of a single species of Enterobacterales, 5 has been reported in many countries such as Korea, the United States, India, and China. [6][7][8] Resistance to carbapenems is associated with several mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the identification of risk factors for CR-ECL infection would improve the choice and effcacy of empirical therapy. 5,7 Therefore, it is urgent to explore the epidemiological characteristics of CR-ECL infection.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, two non-ST78 isolates (TUM17947 and TUM17948) carried bla IMP-1 on IncHI2 plasmids. Carriage of bla IMP-1 on IncHI2 plasmids by ECC isolates of multiple STs (e.g., ST53, 78, 113, 513, 1047) has been documented in another area (Nagoya) in Japan [23]. Although ST78 isolates appears to predominate among IMP-producing ECC isolates in Tokyo according to our previous study, the nationwide epidemiology remains to be elucidated [6].…”
Section: Discussionmentioning
confidence: 85%